Gender-specific peculiarities of bone tissue metabolism in patients with osteoarthrosis - Sinyachenko, Oleg; Dobrovynska, Olena; Tov, Inessa (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
Sexual dimorphism in changes of bone metabolism markers in osteoarthrosis manifests itself by blood levels of parathyrin, hydrocortisone and phosphorus. Here, reliable gender-specific differences in the rate of the above changes concern osteocalcin, hydrocortisone, insulin, phosphorus and magnesium; the indices correlate with the metacarpal index and mineral density of bone, they are mutually dependent upon the severity of osteodestructive changes in joints, spread of articular syndrome, expressiveness of synovitis, and presence of metabolic syndrome.